Death Penalty: The Present Day Threat to Human Life - Phillips, Gerardette (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2014)
The death penalty is not an act of self-defense against an immediate threat to life. It is the premeditated killing of a prisoner who could be dealt with equally well by less harsh means.  There can never be a justification for torture or for cruel, inhumane or degrading treatment or punishment. The cruelty of the death penalty is evident. Like torture, an execution constitutes an extreme physical and mental assault on a person already rendered helpless by government authorities. The most common justification offered is that, terrible as it is, the death penalty is necessary: it may be necessary only temporarily, but, it is argued, only the death penalty can meet a particular need of society. And whatever that need may be, it is claimed to be so great that it justifies the cruel punishment of death. The death penalty, as a violation of fundamental human rights, would be wrong even if it could be shown that it uniquely met a vital social need. What makes the use of the death penalty even more indefensible and the case for its abolition even more compelling is that it has never been shown to have any special power to meet any genuine social need.